Methods of Islamic Guidance and Social Counseling in Overcoming Teenagers’ Psychological Matters Due to Parental Divorce - Andriani, Andriani; Lessy, Zulkipli; Putri, Depi (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2023)
This study aims to highlight the impacts of parent’s divorce on teenagers in Garanta Village, Ujung Loe District, Bulukumba Regency. The study employed a qualitative descriptive approach to provide a broad insight into a phenomenon then was switched to data. Using this approach, the study solicited eight participants of six teenagers, the head of District Religious Affairs Office and a parent. Data were gathered through interviews and observations, and were collected through a process that follows the scientific method including choosing the topic, focusing on research questions, as well as collecting, analyzing, and interpreting the data. The results of the study showed that teenagers disregarded their environment, became depressed, hated parents, felt very irritable, or were very sad. In response to these psychological negativities, Islamic religious educators employed a persuasive approach, delivered guidance, and provided an adequate solution to deal with the profound sadness that has appeared over time since parental separation. This study implies that the Islamic religious instructors should have the professional duty to take a meaningful care. They should establish an outreach program in society for helping those who are vulnerable in the community, especially the parents and teenagers, and both take part in the instruction to accumulate more knowledge to heal the psychological impacts due to the parental separation. Penelitian ini bertujuan untuk melihat dampak dari perceraian yang dirasakan oleh remaja di Desa Garanta Kecamatan Ujung Loe Kabupaten Bulukumba. Penelitian ini menggunakan pendekatan deskriptif-kualitatif yang memberikan pandangan luas dari sebuah fenomena yang dijadikan sebagai data penelitian. Dengan menggunakan pendekatan ini, penelitian ini melibatkan delapan orang yang terdiri dari: enam remaja, kepala KUA dan orang tua. Data diperoleh dengan melakukan interview dan observasi serta diperoleh lewat sebuah proses yang sesuai dengan metode ilmiah seperti: menentukan topik, membuat pertanyaan penelitian, dan juga mengumpulkan, menganalisis, serta menginterpretasi data. Hasil penelitian menunjukkan para remaja bersikap acuh terhadap lingkungan, mengalami tertekan, benci orang tua, mudah marah-marah, atau merasa sedih. Menyikapi kondisi psikologi yang negatif, Penyuluh agama Islam menggunakan tindakan persuasif, memberikan pembinaan, serta mencarikan solusi terbaik dari anak agar tidak berlarut- larut dalam kesedihan yang dialami setelah orang tua mereka bercerai. Penelitian ini memiliki implikasi bahwa Penyuluh Agama Islam secara profesional sebaiknya lebih aktif lagi untuk turun kelapangan, untuk melakukan pendekatan kepada masyarakat khususnya para orang tua serta remaja korban perceraian agar tugas dari para penyuluh juga terlaksana sebagaimana mestinya dan dampak psikologis dari perceraian yang mereka alami akan berkurang.